Concept and Implementation of Participation and Empowerment: Reflection From The Coffee IPM-SECP - Iqbal, Muhammad (Makara Human Behavior Studies in Asia, 2007)
Participation and empowerment are two important keywords in agricultural development program. One of the agricultural programs that considerably implemented through farmer’s participation towards empowerment is Integrated Pest Management (IPM). This article reviews the reflection of the concepts and implementations of farmer’s participation and empowerment in the coffee Integrated Pest Management for Smallholder Estate Crops (IPM-SECP). It can be explained that farmers were participated only in the planning and implementation stages of the project, while monitoring and evaluation activities were solely done by the project implementing unit and other related agencies. In the planning stage, the extent of farmer’s participation can be categorized as pseudo participation since farmers only participated if they were the head of farmer’s group or local model farmers. Meanwhile, in the implementation stage, it was found that farmers had a high extent of participation in the various activities and practices of training carried out by the project. Nevertheless, farmers were empowered in terms of knowledge and skills gained, change in practices, decision-making, productivity, and environmental awareness. As a result, farmer’s participation should be anchored in all stages of planning, implementation, monitoring, and evaluation, so that they would be able to get immediate genuine empowerment feedback of the project impact.